2020
DOI: 10.1186/s12865-020-00349-w
|View full text |Cite|
|
Sign up to set email alerts
|

Ionizing radiation modulates the phenotype and function of human CD4+ induced regulatory T cells

Abstract: Background: The use of immunotherapy strategies for the treatment of advanced cancer is rapidly increasing. Most immunotherapies rely on induction of CD8+ tumor-specific cytotoxic T cells that are capable of directly killing cancer cells. Tumors, however, utilize a variety of mechanisms that can suppress anti-tumor immunity. CD4+ regulatory T cells can directly inhibit cytotoxic T cell activity and these cells can be recruited, or induced, by cancer cells allowing escape from immune attack. The use of ionizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 82 publications
3
23
0
Order By: Relevance
“…Similar to our results, Kajioka et al (1999) have evaluated the responses of CD19 + B cells, CD4 + , and CD8 + lymphocytes against the whole-body radiation on the 3 Gry gamma-radiated mice. Their observations showed significantly less change in the rate of CD19 + B cells and CD4 + and CD8 + lymphocytes in the gamma-radiated mice 28 . Likewise, a more radiosensitive from CD19 + B cells was observed compared to CD4 + and CD8 + lymphocytes 29 .…”
Section: Discussionmentioning
confidence: 92%
“…Similar to our results, Kajioka et al (1999) have evaluated the responses of CD19 + B cells, CD4 + , and CD8 + lymphocytes against the whole-body radiation on the 3 Gry gamma-radiated mice. Their observations showed significantly less change in the rate of CD19 + B cells and CD4 + and CD8 + lymphocytes in the gamma-radiated mice 28 . Likewise, a more radiosensitive from CD19 + B cells was observed compared to CD4 + and CD8 + lymphocytes 29 .…”
Section: Discussionmentioning
confidence: 92%
“…20 Similarly, it has been demonstrated that irradiated Tregs can exhibit a reduced capacity to suppress the proliferation of CD8 + T cells particularly when combined radioimmunotherapies are used. 21 In the present report, Tregs distribution was low and comparable at disease resolution and disease re-progression in the peripheral blood of the patient. In line with our result, it has been demonstrated recently that Tregs with suppressive activity were upregulated on tumor-infiltrating T cells from patients with gastric cancer compared with their expressions on corresponding peripheral blood.…”
supporting
confidence: 55%
“…20 Similarly, it has been demonstrated that irradiated Tregs can exhibit a reduced capacity to suppress the proliferation of CD8 + T cells particularly when combined radioimmunotherapies are used. 21 To this end, we analyzed the presence of the Tregs (CD4 ++ CD25 high FOXP3 + ) population at disease resolution and disease re-progression in the peripheral blood mononuclear cells of the patient. Tregs distribution was low and comparable at both disease stages (online supplementary figure S3).…”
Section: Phenotyping and Functional Characterization Of Patient's T Cmentioning
confidence: 99%
“…For instance, they may suppress the effector immune response and help the tumor grow, whilst downregulating inflammation and thereby protecting the host from tumor progression [28]. Beauford et al [29] revealed that human Tregs from healthy donors are more resistant to radiation-induced death than other immune cells. An increase in FoxP3 cell numbers in the TME is possibly induced by two mechanisms; post-radiation transforming growth factor-β1 (TGF-β1) secretion by cells in the cancer stroma and radioresistance of tumor-infiltrated Tregs.…”
Section: Discussionmentioning
confidence: 99%